Bimbingan Kelompok Bimbingan Kelompok Teknik Self Management Berbasis Experiental Learning Untuk Mengembangkan Adaptabilitas Karier Siswa SMK - Sainda, Ahmad Thoriq Tri; Setiyowati, Arbin Janu; Hambali, IM (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
SMK students need to have good career adaptability skills to be able to cope with career changes, get jobs quickly without experiencing long-term unemployment, and be able to find jobs that match their personalities and skills. The purpose of this study was to evaluate the effectiveness of self-management technique group counseling services using the experiential learning method in developing career adaptability of SMK students. This study used a pretest-posttest control group design. A total of 20 students became research subjects who had a moderate level of career adaptability, and they were divided into two groups, namely the experimental group and the control group. The results of data analysis using the SPSS program on the Mann-Whitney U Two-Independent-Sample Test showed the value of Asymp. Sig of 0.020 (0.020 <0.050). These results indicate that there is a difference in the level of career adaptability between the interventions given to the experimental group and the control group, which indicates that self-management group counseling services with experiential learning methods are more effective in developing the career adaptability of SMK students.